2019
DOI: 10.3390/jcm8060908
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraceptives, Female Sexual Dysfunction, and Managing Strategies: A Review

Abstract: In recent decades, hormonal contraceptives (HC) has made a difference in the control of female fertility, taking an unequivocal role in improving contraceptive efficacy. Some side effects of hormonal treatments have been carefully studied. However, the influence of these drugs on female sexual functioning is not so clear, although variations in the plasma levels of sexual hormones could be associated with sexual dysfunction. Permanent hormonal modifications, during menopause or caused by some endocrine patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 56 publications
0
50
0
4
Order By: Relevance
“…The combined oral contraceptives agents are known increase the hepatic production of SHBG (40,41). Many studies suggest that this is one of the reasons why the use of combined oral contraceptives reduce libido, since excess SBGH would decrease the free testosterone fraction in women, directly affecting sexual function (14,15). After stop using combined oral contraceptives a decrease in SGBH would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…The combined oral contraceptives agents are known increase the hepatic production of SHBG (40,41). Many studies suggest that this is one of the reasons why the use of combined oral contraceptives reduce libido, since excess SBGH would decrease the free testosterone fraction in women, directly affecting sexual function (14,15). After stop using combined oral contraceptives a decrease in SGBH would be expected.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Nevertheless, a review done in 2019 found that hormonal contraceptives have a contradictory effect on sexual dysfunction. 24 Newer hormonal contraception, such as the patch and the levonorgestrel (LNg) intrauterine device, have been documented to have less effect on sexual desire. 24 …”
Section: Discussionmentioning
confidence: 99%
“… 24 Newer hormonal contraception, such as the patch and the levonorgestrel (LNg) intrauterine device, have been documented to have less effect on sexual desire. 24 …”
Section: Discussionmentioning
confidence: 99%
“…The combined oral contraceptives agents are known increase the hepatic production of SHBG (40,41). Many studies suggest that this is one of the reasons why the use of combined oral contraceptives reduce libido, since excess SBGH would decrease the free testosterone fraction in women, directly affecting sexual function (14,15). After stop using combined oral contraceptives a decrease in SGBH would be expected.…”
Section: Discussionmentioning
confidence: 99%